SOSIALISASI PELUANG DAN TANTANGAN BERWIRAUSAHA DI ERA 4.0 PADA SISWA SMA SETIA MARGA SAMARINDA - Suyanto Suyanto; Tiara Sahita (Journal of Empowerment and Community Service (JECSR), 2022)
The millennial era is an era in which existing generations have become more "brutally" aggressive in the history of human civilization. The behavior and mindset of the millennial generation have changed drastically due to exposure to today's massive technology and digital world. The millennial era encourages the existence of a new group of people with the category "Other than Others" and is not linearly related to the changes that occurred in previous generations. Baby boomers to Gen-X are linear and carry on from the previous generation. In the business world (entrepreneurship), business people are faced with two twin realities, namely, digital disruption and millennial disruption, both of which have a deadly effect on conventional business. There are more than 20 products, services, companies, industries, and habits that will be left behind by the millennial generation, so businesses must change their strategy from conventional to digital by first understanding how the concept of change must be prepared.